Tiltawhirl John - Paulsen, Gary. (New York : Puffin Books, 1990)
A fifteen-year-old runaway discovers that a carnival's razzle-dazzle doesn't shield it from the cruelties of life.
6.0
5-8
Keywords: Carnivals -- Fiction; Runaways -- Fiction; Carnivals -- Fiction; Runaway teenagers -- Fiction